Hemorrhagic giant intra-abdominal desmoid tumor in twin pregnancy: a case report and literature review - Wang, Shizhao; Du, Zeqing; Huang, Lining; Liu, Xiao (Frontiers in Oncology, 2025)
BackgroundDesmoid tumors (DTs) are rare, non-metastatic fibroblastic neoplasms known for their local invasiveness and slow growth. Their occurrence during pregnancy is rare, presenting unique diagnostic and therapeutic challenges, especially when complications like hemorrhage develop. Spontaneous hemorrhage in intra-abdominal DTs is an exceptionally rare complication.Case presentationWe report a 31-year-old woman, 32 + 4 weeks into a twin pregnancy, with a history of successful IVF-ET and routine prenatal care, who presented with acute left abdominal pain and signs of hemorrhagic shock. A computed tomography (CT) scan revealed a giant intra-abdominal mass (23.6×15.6×17.3 cm) with active bleeding. An emergency cesarean section and tumor resection were performed, which revealed a desmoid tumor (DT) invading the pancreas and transverse colon. Postoperative recovery was uneventful, and the patient was discharged in stable condition.ConclusionThis case underscores the importance of early multidisciplinary intervention in managing rare pregnancy-associated desmoid tumors (DT) complicated by hemorrhage. It emphasizes the necessity of heightened clinical suspicion in pregnant women presenting with acute abdominal pain.